Protocol for a Cluster Randomized Controlled Trial to Reduce Susceptibility to Tobacco Use Among School Going Adolescents in a South-Indian District—(Project TEACH) - Priyanka Bantwal; Veena G Kamath; John Britton; Ilze Bogdanovica; Manjula A Kunder; Samir K Praharaj; Muralidhar M Kulkarni (Indian Journal of Psychological Medicine)
Background: Adolescents are susceptible to using tobacco because of early exposure to tobacco through family members, easy access, or peer pressure. School-based educational programs are crucial for raising awareness of the harms of tobacco, thus preventing its uptake among adolescents. Studies conducted recently have recognized the need to bring change and reinforce ongoing school-based anti-tobacco education programs. Our study protocol aims to evaluate the effectiveness of a revised school-based anti-tobacco education on susceptibility to tobacco use among school-going adolescents. Method: Project TEACH (Tobacco Education and Awareness for Creating Healthier Adolescents) is an educational intervention that will comprise an animated video on the effects of tobacco on physical and mental health, along with dispelling myths about tobacco, which will be delivered along with a standard education program. The control group will only receive the standard school-based anti-tobacco education program. It will be conducted among students between 6 th to 10 th grade, with a sample size of 3,310 students. Results: Bivariate relations between the main socio-demographic characteristics and susceptibility to tobacco use will be tested using Pearson or Spearman’s correlation coefficients. For multivariable analyses, the binary logistic regression analysis is used to establish a risk model to correlate the socio-demographic factors with susceptibility to tobacco use and awareness of the harms of tobacco. Conclusion: Project TEACH aims to provide a sustainable school-based anti-tobacco education intervention. It will help test the effectiveness of the revised intervention, which could be incorporated into the current school education program being conducted in the district.